Aan de tijd ontstegen: E.J. Dijksterhuis (1892–1965) en De mechanisering van het wereldbeeld - van Berkel, Klaas (Studium, 2013)
Aan de tijd ontstegen: E.J. Dijksterhuis (1892–1965) en De mechanisering van het wereldbeeld